Arab Female Diasporic Writing: Towards An Annihilation Of Debasement - Rahmani , Mokhtaria (El Omda in Linguistics and Discourse Analysis, 2023)
Post colonial diasporic literature was tailored for reflecting on the host country/native country binary with its myriad by-products as displacement and identity crisis. At this juncture, Arab women emphasized rather gender reconsideration. Thus, many female writers as Hanan Al-Shaykh , Salwa al-Neimi, Joumanna Haddad, and Assia Djebar, employed literature to denunciate forms of oppression, basically patriarchal. Such rebelling themes were, undoubtedly, unleashed by diasporic leverages. Thus, the premise motivating this paper is to see the extent of influence exercised by Western settings in triggering this development. A descriptive-analytical method was used to scrutinize the corpus study selected (The Story of Zahra, Women of Sand and Myrr, The Proof of Honey, I Killed Scheherazade: Confessions of an Angry Arab Woman, and Femmes d’Alger dans leur Appartements,). The findings demarcate the high socio-cultural and political engagement of female writers in the diaspora born out by the impress of Western thought.